The theory of cameralism of Platonov and Jakob from Kharkiv Imperial University and Yusti, Zonnenfels from Vienna University - Пересада, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
In current article, cameralism is considered as science of government administration. Political science have been in different hypostasis during all existence of university and because of that fact, current work dedicated to disclose it in terms of cameralism. The theory of cameralism was developed during XVIII century in Vienna University and later in Kharkiv University. Professor’s ideas about cameralism was clodely connected with actual state political and economic agenda and practical implementation of comeralism ideas by government.